Evolutionary Music; Composing Beats and Chords Progression - Ng, Hayden (2020)
This project focuses on delivering a JAVA application named “Evoluthm” with mainly the functions of generating chords progressions and beats. The system aims to aid in inspiring music composer and also generate music based on the requirements or needs of the music composer. For instance, the music’s speed, pitch range, number of layers, number of notes to be generated and different types of music instruments can be selected. Evoluthm utilizes Harmony Search Algorithm and JFUGUE techniques in compliances with artificial intelligence (AI). These techniques are used in success to produce a perfect music or melody and minimizes the number of error melodies. Thus, Evoluthm is a tool to help musician to obtain inspiration from random generated melodies to compose a new piece of music.